2007
DOI: 10.1158/0008-5472.can-06-3369
|View full text |Cite
|
Sign up to set email alerts
|

Dikkopf-1 as a Novel Serologic and Prognostic Biomarker for Lung and Esophageal Carcinomas

Abstract: Gene expression profile analysis of lung and esophageal carcinomas revealed that Dikkopf-1 (DKK1) was highly transactivated in the great majority of lung cancers and esophageal squamous cell carcinomas (ESCC). Immunohistochemical staining using tumor tissue microarrays consisting of 279 archived non-small cell lung cancers (NSCLC) and 280 ESCC specimens showed that a high level of DKK1 expression was associated with poor prognosis of patients with NSCLC as well as ESCC, and multivariate analysis confirmed its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
183
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(193 citation statements)
references
References 41 publications
7
183
1
2
Order By: Relevance
“…Thereby, Dkk1 might be the key factor for promoting tumour metastasis by downregulating membrane LRP5/6. Notably, cancer patients with Dkk1 upregulation have long been known to have poorer prognosis, although the reason remains unknown 37 . Our present findings also show a higher expression of Dkk1 in 4T1-implanted primary tumour than metastases, and no expression of Dkk1 was detected in neighbouring normal lung tissues ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, Dkk1 might be the key factor for promoting tumour metastasis by downregulating membrane LRP5/6. Notably, cancer patients with Dkk1 upregulation have long been known to have poorer prognosis, although the reason remains unknown 37 . Our present findings also show a higher expression of Dkk1 in 4T1-implanted primary tumour than metastases, and no expression of Dkk1 was detected in neighbouring normal lung tissues ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…11 DKK-1 is a secreted protein and readily detectable in the circulation. [12][13][14][15][16] Therefore, it is hypothesized that DKK-1 levels in circulation or ocular fluid could be associated with the development and progression of DR.…”
Section: Introductionmentioning
confidence: 99%
“…As a secreted protein, DKK1 is elevated in serum from patients with diverse malignancies. In lung cancer, DKK1 was found to be a novel serologic and histochemical biomarker, as well as a therapeutic target (Yamabuki et al, 2007). Shen et al found DKK1 to be elevated in hepatocellular carcinoma, where it complemented measurement of AFP in the diagnosis of HCC (Shen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Next, the 35 remaining full manuscripts were retrieved for detailed evaluation. Finally, 10 manuscripts in total (Yamabuki et al, 2007;Jiang et al, 2009;Sheng et al, 2009;Sato et al, 2010;Shen et al, 2010;Soydinc et al, 2011;Tung et al, 2011;Lee et al, 2012;Shen et al, 2012;Shi et al, 2013), which consisted of 11 studies, were included for evaluation according to the inclusion and exclusion criteria. The remaining 25 studies were excluded because of: a) lack of sufficient data (n=5); b) duplicate publications (n=12); c) lack of a control group (n=3); d) being a review article (n=2); or e) printed in Chinese (n=3).…”
Section: Eligible Articles For Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation